A EDUCAÇÃO INFANTIL E A OBRIGATORIEDADE: O QUE PROPÕEM OS PMEs DE QUATRO MUNICÍPIOS DA REGIÃO DE GUARAPUAVA/PR? - PROÊNCIO, LILIAN MARTINS DE (2019)
This paper aims to identify and problematize the strategies of the Municipal Education Plans (MEPs) of four cities in the region of Guarapuava (PR) related to the required enrollment in early childhood education. The research falls within the scope of the discussions of the Study Group and Research in Early Childhood Education / GEPEDIN. It is a qualitative research, with document analysis of the Municipal Education Plans. As specific objectives, it sought to recognize the educational policies for childhood, especially the elements and factors involved in their formulation and the underlying interests; situate early childhood education as a right of all children and analyze the legislation that indicates the required pre-school enrollment and the impacts of its implementation; analyze the MEPs of four cities with a view to recognize the strategies indicated to make required pre-school enrollment effective. We start from the understanding of the elaboration process of public policies, with a special look at the course of the policies for Early Childhood Education, in order to focus on the intentions explained in the analyzed Plans. In these, the strategies related to the expansion of vacancies, infrastructure, working hours and teacher training were observed, aspects that need to be considered in the concept of quality in early childhood education. Data analysis revealed that MEPs present strategies that address these points, but they do so in a very generic way, which would allow different interpretations. As for the expansion of vacancies, it is foreseen in the documents, but it is questionable since the preschool children are being attended, mostly, in classes in institutions that used to attend only the Elementary School, and for this, structural issues need be adapted to meet the needs of children. The working hours were reduced to part-time and the professionals, although mostly have higher education, need referrals to ensure continuing education. We conclude, therefore, that MEPs are important instruments in the registration and commitment of municipal management strategies, however they need to be more clearer, with provision for referrals and delimitation of responsibilities, as well as requiring the whole community to monitor implementation, considering the right of all children to a quality early childhood education.